Ultrathin Semiconductor Superabsorbers from the Visible to the Near‐Infrared. Issue 9 (12th January 2018) - Molet, Pau; Garcia‐Pomar, Juan Luis; Matricardi, Cristiano; Garriga, Miquel; Alonso, Maria Isabel; Mihi, Agustín
Abstract: The design of ultrathin semiconducting materials that achieve broadband absorption is a long‐sought‐after goal of crucial importance for optoelectronic applications. To date, attempts to tackle this problem consisted either of the use of strong—but narrowband—or broader—but moderate—light‐trapping mechanisms. Here, a strategy that achieves broadband optimal absorption in arbitrarily thin semiconductor materials for all energies above their bandgap is presented. This stems from the strong interplay between Brewster modes, sustained by judiciously nanostructured thin semiconductors on metal films, and photonic crystal modes. Broadband near‐unity absorption in Ge ultrathin films is demonstrated, which extends from the visible to the Ge bandgap in the near‐infrared and is robust against angle of incidence variation. The strategy follows an easy and scalable fabrication route enabled by soft nanoimprinting lithography, a technique that allows seamless integration in many optoelectronic fabrication procedures. Abstract : A nanostructured 70 nm dielectric superabsorber on metal is designed and fabricated with a photonic structure rendered with ultimate light‐trapping capabilities reaching integrated absorption of 81% in a broadband range from 400 to 1500 nm. Highly scalable nanopatterning techniques (soft lithography) are used, and wide absorption tunability is demonstrated, making it a great system for photosensing and photocatalysis.